2018
DOI: 10.1038/s41598-018-29233-9
|View full text |Cite
|
Sign up to set email alerts
|

A dual-fMRI investigation of the iterated Ultimatum Game reveals that reciprocal behaviour is associated with neural alignment

Abstract: Dyadic interactions often involve a dynamic process of mutual reciprocity; to steer a series of exchanges towards a desired outcome, both interactants must adapt their own behaviour according to that of their interaction partner. Understanding the brain processes behind such bidirectional reciprocity is therefore central to social neuroscience, but this requires measurement of both individuals’ brains during real-world exchanges. We achieved this by performing functional magnetic resonance imaging (fMRI) on pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…The Ultimatum Game task was previously used in an fMRI study by Shaw et al (26). It presents a simple paradigm to investigate dyadic interaction.…”
Section: Ultimatum Game Taskmentioning
confidence: 99%
“…The Ultimatum Game task was previously used in an fMRI study by Shaw et al (26). It presents a simple paradigm to investigate dyadic interaction.…”
Section: Ultimatum Game Taskmentioning
confidence: 99%
“…behavioral coupling with the VP) and correct attribution of the VP's intentions. Corresponding brain analysis reveals how anterior areas coordinate their activity with frontal and prefrontal areas, the latter generally recruited in decision-making tasks regardless of the presence of others (Tomlin et al, 2006;Campbell-Meiklejohn et al, 2017;Shaw et al, 2018;Thornton et al, 2019).…”
Section: Brain Dynamics Of Social Embodimentmentioning
confidence: 99%
“…A network of frontal activations incorporating the dorsal ACC and AI constitute the so-called salience network, which is thought to be responsible for identifying behaviorally relevant stimuli. In a previous study, we observed a similar pattern of neural alignment within the dorsal ACC and AI between players involved in an interactive game of economic exchange; more specifically, inter-brain alignment in these regions was associated with the degree of reciprocity expressed between players (Shaw et al, 2018). We interpreted this to reflect the mutual effort of players to modify their own behavior according to that of their opponent, a process necessary to compete successfully in an inter-dependent context.…”
Section: Discussionmentioning
confidence: 61%
“…With these techniques, studies have revealed various patterns of neural coupling elicited during social interaction; while temporally contingent brain responses are observed between interactants during verbal and non-verbal communication (Ahn et al, 2017;Bilek et al, 2015;Pérez, Carreiras, & Duñabeitia, 2017), between-brain synchrony or "alignment" (Hasson & Frith, 2016) is reported during cooperative and competitive joint-action tasks (e.g., Cheng, Li, & Hu, 2015;Sänger, Müller, & Lindenberger, 2012;Shaw et al, 2018;Toppi et al, 2016).…”
mentioning
confidence: 99%